Adsorption of congo red using kaolinite-cellulose adsorbent - Santa Oktavia Ginting; Risfidian Mohadi (Science and Technology Indonesia, 2017)
Kaolinite was impregnated with cellulose extracted from rubber wood fibers has been done. The product of impregnated kaolinite-cellulose was characterized using FT-IR spectrophotometer. Furthermore, the impregnation results are used as an adsorbent of Congo red. Adsorption of Congo red was also studied the kinetic and thermodynamic parameters. The results of characterization using FT-IR spectrophotometer shows the process of impregnation was successfully conducted. It was indicated that the presence wavenumber at 910.4 - 918.12 cm-1 and 1033.85 cm-1 become 1026.13 cm-1 and the existence of vibration at wavenumber 2931.8 cm-1. The pH of adsorption was adjusted to 4 before the adsorption process. The adsorption process of cellulose impregnated kaolinite shows the rate of adsorption (k) of 0.002 min-1, the adsorption reviews largest capacity (b) at 50 °C was 500 mol/g. The greatest adsorption energy (E) at 40 °C is 11:09 kJ/mol. The enthalpy value (ΔH) and entropy (ΔS) decreased with increasing Congo red dye concentration. Keywords: kaolinite, cellulose, impregnation, Congo red